A LearningApps használata Magyarországon - tankockázzon velünk! - Ládiné Szabó Tünde Julianna (Módszertani közlemények, 2017)
Learningapps.org is a web 2.0 application to support learning and teaching. You can create interactive and multimedia teaching materials, teaching blocks that can be changed using an online platform in a simple way. LearningApps.org versatile tool for teaching and for independent practice at home or on the road.